Adversity Quotient Arranging Thesis for Students of Faculty of Education State University of Padang - Lailatus Soniatri; Yarmis Syukur (Universitas Negeri Padang, 2019)
This research is motivated by the existence of underprivileged students find reference in research, then students are not able to communicate well when meeting with supervisors, and students have difficulty understanding the research concepts. This study aims to describe the adversity quotient in preparing thesis for students in terms of: (1) control, (2) origin and ownership, (3) reach, and (4) endurance.This research uses quantitative methods with descriptive type. The sample in this study were 267 people selected using the Proportional Random Sampling technique. The research instrument used was the adversity quotient questionnaire composing the thesis using a Likert scale. Data were processed using descriptive statistical analysis techniques. The results of the study revealed that: (1) adversity quotient compiling thesis for FIP UNP students is in the high enough category (2) in the control aspect is in the high enough category, (3) in the origin and ownership aspects are in the high enough category, (4) the reach aspect is in the high enough category, and (5) the endurance aspect is in the quite high category. Based on the research findings, it is suggested to the Counselor at the University to be able to provide guidance and counseling services in the form of information services, individual counseling, and group counseling, in order to assist students in alleviating problems that are being experienced by these students and to increase adversity quotient.